The Role of Inhibition of Apoptosis in Acute Leukemias and Myelodysplastic Syndrome - McBride, Amanda; Houtmann, Sarah; Wilde, Lindsay; Vigil, Carlos; Eischen, Christine M.; Kasner, Margaret; Palmisiano, Neil (Frontiers in Oncology, 2019)
Avoidance of apoptosis is a key mechanism that malignancies, including acute leukemias and MDS, utilize in order to proliferate and resist chemotherapy. Recently, venetoclax, an inhibitor of the anti-apoptotic protein BCL-2, has been approved for the treatment of upfront AML in an unfit, elderly population. This paper reviews the pre-clinical and clinical data for apoptosis inhibitors currently in development for the treatment of AML, ALL, and MDS.